Colaterales del arco aórtico del cuilo Cavia Porcellus (Rodentia) - Quesada, Rafael; Madriz, Luis Fdo.; Fernandez, Walter A. (Revista de Biología Tropical, 1986)
The distribution of the principle arteries of the aortic arch in male and female guinea pigs is highly variable.